DEVELOPMENT TRENDS OF GEORGIAN CAPITAL MARKET AND PENSION FUND (International Journal of Innovative Technologies in Economy, 2024)
Since January 2019, a cumulative pension system has been launched in Georgia. The reform’s main goals are reducing fiscal pressure and ensuring a "decent" pension at retirement age. In addition, the possible positive impact of the accumulated pension fund on the capital market of Georgia is important. The purpose of the paper is to analyze the current reality of the capital market of Georgia. In order to determine what opportunities it creates in the investment process of the Georgian pension agency. During the research, we mainly used statistical analysis methods. The discussion is based on indicators such as: composition of total debt of non-financial companies in Georgia; liquidity and activity on the Georgian stock exchange; total balance of corporate bonds denominated in GEL; the ratio of the total capitalization of the stock market; assets of the Georgian pension agency and its investment portfolio. Due to research findings, although there is a lack of institutional investors in the financial markets of Georgia, there are no existing securities in the local market, which would allow the pension agency to make more investments in the local capital market. Growth at such a rate requires investing in assets with a higher risk than the existing ones. In particular, since the capital market assets have a higher rate of return, it is important for the policy of the pension agency to either increase the limits for investing in the foreign market, or to be more opportunities and alternatives in the local capital market.